Using a Chatbot to Study Medication Overuse Among Patients Suffering From Headaches - Bézie, Arthur; Morisseau, Valentin; Rolland, Romain; Guillemassé, Arthur; Brouard, Benoît; Chaix, Benjamin (Frontiers in Digital Health, 2022)
According to the World Health Organization, half of the adult population around the world suffer from headaches. Even though this condition remains in most cases innocuous, it can have a major impact on patients’ quality of life but also on public health expenditure. Moreover, most patients manage their headaches on their own, without consulting a doctor. Self-medication can eventually lead to drug overuse and the emergence of a secondary disease called a medication-overuse headache. The detection and follow-up of these unconventional patients represent a major challenge. Some of the latest technologies seem to be tailored to this context. The goal of this study is to investigate medication overuse in French patients suffering from headaches using the chatbot Vik Migraine to collect and analyze data through a questionnaire. It was made of 28 questions divided in three parts: the socio-demographic profile, drug consumption, and medical follow-up. The study showed that medication overuse was often linked with increased headaches’ frequency. Triptans and opioids, which are prescription drugs, were the most overused drugs among the cohort. This suggests that healthcare professionals could play a role in the prevention of drug overuse.